The CDH patient perspective journey - Power, Beverley (Frontiers in Pediatrics, 2023)
‘The CDH Patient Journey’ Beverley Power et al Chairperson of CDH UK The Congenital Diaphragmatic Hernia Charity Founding member IDEA Alliance SCANS member Patient Representative ERNICA Background Congenital Diaphragmatic Hernia is a malformation of the diaphragm resulting in ongoing clinical symptoms and problems. Mortality remains high, particularly where there are other issues involved. Tracking a patient throughout their lifetime to understand the full impact on health and function is challenging. CDH UK is a registered charity supporting anyone affected by CDH. It has over 25 years of experience and a broad range of patient experience and knowledge. Aims To develop a patient journey with timepoints of significance. Methods We studied our own data and looked at what we already knew from publications and medical advisors. We recruited a focus group, plotted out stages and timepoints through their ‘lived’ experiences using the Team Idea Mapping method. We then compared these experiences to our own data, to identify the common issues in daily life and care. Outcome We have developed a patient journey through the eyes of the patient and turned it into a patient friendly infographic. This can be used as a tool to help understand the CDH Journey throughout a patient’s lifetime. CDH UK has already used this to create a first prototype of a mobile application. It has also further helped to recognise areas of patient concern and to improve services and resources. Discussion This can be used as a basis for care and research, including standards, benchmarking, transition and helping improvements in healthcare, education, family life and social settings. Potentially holding clues as to the etiology and pathology of the condition and an opportunity to further explore theories and unanswered questions. It may help improve counselling and bereavement care, resulting in better general and mental health outcomes.